Oncology Referral Concerning Paediatric Neurosurgery? Analysis of the Situation between 2008-2013 in the North of Portugal - Ana Batista; Luís Nogueira-Silva; Rui Vaz; Joana Oliveira (Acta Médica Portuguesa, 2016)
Introduction: Primary central nervous system tumours represent the second most frequent neoplasm and are the leading cause of death from solid tumours in children. Our study aimed to provide the most up-to-date epidemiological analysis of primary central nervous system tumours in children living in the north of Portugal and to explore a possible effect of the centralisation of care on outcomes. Material and Methods: This population-based study included all newly diagnosed and histologically confirmed primary central nervous system tumours in people below 18 years old, living in the north of Portugal, from January 2008 to December 2013. Data were collected through access to clinical files. We described children and tumour characteristics, and analysed patient: paediatric neurosurgeon and histological tumour type: paediatric neurosurgeon ratios. Results: A total of 147 cases was recorded. Mean age at diagnosis of primary central nervous system tumours was 8.0 ± 5.2 years. Astrocytomas were the most common histological type (34%). We found that World Health Organization Tumour Grade was the only variable of statistically significant influence in mortality (p = 0.001). 1-, 3- and 5-year survivals related to 2008-2013 period were statistically higher than 2005 - 2007. Astrocytomas have the highest survival rate, with statistically significant difference from other tumours (p = 0.015). We estimated a mean of 12.25 treated cases per year by each paediatric neurosurgeon at our institution. Discussion: Our results are globally consistent with those published all over the world, but we reported the highest survival rates. The number of cases treated per year by each neurosurgeon is accordant to the recommended. Conclusion: We showed an improvement when comparing to data previous to 2008 and better results than those from previous studies, namely higher survival at 1-, 3- and 5-years from the diagnosis, with low complication and relapsing rates. Therefore, the referral of primary central nervous system tumours cases to centres with larger experience can be invaluable for the achievement of the best outcomes.